Cooperation among Microorganisms - Wingreen, Ned S (Public Library of Science, 2006)
Understanding cooperation among microorganisms presents conceptual and mathematical challenges at the interface of evolutionary biology and the theory of emergent properties of independent agents, two of the most exciting areas in modern mathematical biology.